Pengaruh Literasi Keuangan, Dan Inklusi Terhadap Ketahanan Keuangan Pada Lembaga Keuangan Bagi Kemakmuran Para Petani Desa Tanjungan Kecamatan Driyorejo - Dian Amanda; Moch. Abid Atoillah Maulana; Yoel Rastafel; Maria Yovita R. Pandin (CV. ULIL ALBAB CORP, 2024)
The aim of this research is to determine the effect of financial literacy on financial resilience that occurs in institutions as a means of capital for farmers, especially in Tanjungan Village, Driyorejo District. In this way, farmers can more easily access capital available from financial institutions, thereby increasing farmers' production results. In this research, the method used is a quantitative approach and multiple linear regression analysis techniques. The results of this research show that financial literacy and inclusion have a positive effect on Financial Resilience in Financial Institutions to support financial capital for the businesses of farmers in Tunjungan Driyorejo Village.